2016
DOI: 10.1016/j.yhbeh.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous testosterone and mating context on men's preferences for female facial femininity

Abstract: Correlational research suggests that men show greater attraction to feminine female faces when their testosterone (T) levels are high. Men's preferences for feminine faces also seem to vary as a function of relationship context (short versus long-term).However, the relationship between T and preferences for female facial femininity has yet to be tested experimentally. This thesis examined the causal role of T in modulating preferences for facial femininity across both short and long-term mating contexts, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 111 publications
(165 reference statements)
1
23
2
Order By: Relevance
“…However, previous work from our lab examining men has found that a single administration of testosterone can increase threat-related amygdala, hypothalamic, and periaqueductal gray reactivity to angry facial expressions within 90 min post administration [63], and effects of testosterone on aggressive behavior are found within 60 min post administration [27]. We also find similar behavioral effects from exogenous testosterone administration on men's preferences for feminine faces when tested at 2 and 3 h post administration [64], as well as effects on selfperceived dominance tested at 2 and 4 h post administration [65]. That effects in the present study are found within 60 min suggests the possibility of a non-genomic mechanism, similar to findings in animal models with rapid effects of testosterone on brain function and behavior (reviewed in [66]).…”
Section: Limitations and Future Directionssupporting
confidence: 73%
“…However, previous work from our lab examining men has found that a single administration of testosterone can increase threat-related amygdala, hypothalamic, and periaqueductal gray reactivity to angry facial expressions within 90 min post administration [63], and effects of testosterone on aggressive behavior are found within 60 min post administration [27]. We also find similar behavioral effects from exogenous testosterone administration on men's preferences for feminine faces when tested at 2 and 3 h post administration [64], as well as effects on selfperceived dominance tested at 2 and 4 h post administration [65]. That effects in the present study are found within 60 min suggests the possibility of a non-genomic mechanism, similar to findings in animal models with rapid effects of testosterone on brain function and behavior (reviewed in [66]).…”
Section: Limitations and Future Directionssupporting
confidence: 73%
“…Furthermore, although we positioned some of these other tasks before the threat premium, we previously found similar testosterone effects on face-processing and decision-making tasks regardless of whether the tasks occurred earlier or later in the testing protocol and the number and types of other, preceding tasks (e.g. [22,23]), suggesting the hormone acted over and above potential fatigue and carry-over effects. 4 Note that these analyses do not include the seven participants for whom we excluded data from the second testing day (see Participants section).…”
Section: Ethics All Procedures Were Approved By the Nipissing Univermentioning
confidence: 74%
“…All samples were assayed in duplicate consistent with standard, 1 But cf. Bird et al, 2016 andCarré et al, 2017 for evidence that topical testosterone gel increases testosterone and produces measurable physiological differences within an hour postgel-administration. published procedures (Schultheiss & Stanton, 2009) using commercial enzyme immunoassay kits (DRG Inc., Germany).…”
Section: Salivary Hormone Measurementmentioning
confidence: 99%